Chaos and complexity in the fisheries management context - Ferreira, M. A. M.; Filipe, J. A.; Coelho, M. (Acta Scientiae et Intellectus, 2017)
Chaos Theory and nonlinear dynamic systems’ models huge importance is recognized beyond any kind of considerations in the most varied research fields. Chaos Theory contributes very significantly to the study of marine systems and fish stocks’ preservation. In this paper are presented clues to manage fisheries in view of chaos contextualization. Particularly, when applied in the situation of ecological systems, especially in the context of fisheries, highlights its recognition in the explanation of fishing phenomena.